2001
DOI: 10.1007/s004640080197
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic thyroid resection using cutaneous elevation in lieu of insufflation

Abstract: Endoscopic surgery of the neck is safe, minimally invasive, and produces excellent cosmetic results. However, it is in an early stage of development. Techniques have yet to be standardized, and specialized instruments are not available. The field is likely to mature as surgeons gain more experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 10 publications
1
60
0
3
Order By: Relevance
“…However, several reports about the application of endoscopic thyroidectomy for PTMC patients in the low-risk group have emerged. Kitano et al [10] reported that indications for endoscopic thyroidectomy in thyroid carcinoma are as follows: (1) age <45 years, (2) tumor size <2 cm, and (3) no evidence of lymph node or local invasion. Miccoli et al [9] showed that there was no difference between conventional open thyroidectomy and endoscopic thyroidectomy in surgical completeness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several reports about the application of endoscopic thyroidectomy for PTMC patients in the low-risk group have emerged. Kitano et al [10] reported that indications for endoscopic thyroidectomy in thyroid carcinoma are as follows: (1) age <45 years, (2) tumor size <2 cm, and (3) no evidence of lymph node or local invasion. Miccoli et al [9] showed that there was no difference between conventional open thyroidectomy and endoscopic thyroidectomy in surgical completeness.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Miccoli et al [9] attempted to perform endoscopic surgery on patients with papillary thyroid carcinoma [9]. Thereafter, many trials involving endoscopic thyroidectomy for thyroid carcinoma with low-risk patients have been reported [10]. We also introduced a novel method of gasless endoscopic thyroidectomy using a trans-axillary approach and early surgical outcomes of patients with benign and malignant thyroid diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is comparable to open technique and comparable to other series (Table 3). [11][12][13] Mean operative time was 88.19 min. Author calculated the time required for surgery for first 10 cases, next 10 cases and last 6 cases, which decreased sequentially.…”
Section: Discussionmentioning
confidence: 99%
“…Most difficulties can be avoided or overcome thanks to the knowledge built on surgical training and ongoing experience. The learning curve is very steep, but it has been proven that the length of surgery decreases with surgical experience, and may possibly improve with advances in surgical instruments [34].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%